PROSPEK DESTINASI WISATA HALAL BERBASIS OVOP (ONE VILLAGE ONE PRODUCT) - M. ZAKY MUBARAK LUBIS (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Indonesia is a rich and beautiful country to natural tourism destinations, one of which is the area of West Sumatra. West Sumatra belongs to the four categories of